2007
DOI: 10.1530/eje-07-0369
|View full text |Cite
|
Sign up to set email alerts
|

The use of 18-fluoro-dihydroxyphenylalanine and 18-fluorodeoxyglucose positron emission tomography scanning in the assessment of metaiodobenzylguanidine-negative phaeochromocytoma

Abstract: I-Metaiodobenzylguanidine (123 I-MIBG) scintigraphy scanning is commonly used in the imaging of phaeochromocytoma (and paraganglioma) to confirm the site of disease and whether any spread has occurred. However, 123 I-MIBG imaging is negative in 15% of cases of benign phaeochromocytoma and around 50% of cases of malignant phaeochromocytoma. In recent years, positron emission tomography (PET) scanning using various different radiotracers has been shown to be a good alternative or supplementary investigation in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 8 publications
1
19
0
1
Order By: Relevance
“…Nonetheless, we found the combination of MRI and 123 I-MIBG to be sufficient in most cases. Although Timmers et al (2007a) recently reported the superiority of 18 F-fluorodeoxyglucose positron emission tomography ( 18 F-FDG PET) in the evaluation of metastatic paraganglioma, one might argue that in our cohort, because most of the paragangliomas were benign, the use of 18 F-fluorodopamine or 18 F-fluoro-dihydroxyphenylalanine ( 18 F-FDOPA) PET would be more appropriate after negative MIBG imaging (Pacak et al 2001, Hoegerle et al 2002, Hoegerle et al 2003, Mackenzie et al 2007). In our study, the sensitive and specific assays for O-methylated catecholamine metabolites (metanephrine and normetanephrine) were introduced for screening only in the last few years.…”
Section: B Havekes Et Al: Screening In Sdhd Patientsmentioning
confidence: 89%
“…Nonetheless, we found the combination of MRI and 123 I-MIBG to be sufficient in most cases. Although Timmers et al (2007a) recently reported the superiority of 18 F-fluorodeoxyglucose positron emission tomography ( 18 F-FDG PET) in the evaluation of metastatic paraganglioma, one might argue that in our cohort, because most of the paragangliomas were benign, the use of 18 F-fluorodopamine or 18 F-fluoro-dihydroxyphenylalanine ( 18 F-FDOPA) PET would be more appropriate after negative MIBG imaging (Pacak et al 2001, Hoegerle et al 2002, Hoegerle et al 2003, Mackenzie et al 2007). In our study, the sensitive and specific assays for O-methylated catecholamine metabolites (metanephrine and normetanephrine) were introduced for screening only in the last few years.…”
Section: B Havekes Et Al: Screening In Sdhd Patientsmentioning
confidence: 89%
“…Furthermore, MIBG may miss additional HNPs in hereditary syndromes. 18 F-FDOPA PET was found to be more sensitive than MIBG scintigraphy in the staging and restaging of paragangliomas (42,50,(54)(55)(56)(57)(58)(59). In some studies, 18 F-FDOPA PET significantly detected more lesions than CT/MRI.…”
Section: Extraadrenal Retroperitoneal Paragangliomasmentioning
confidence: 99%
“…From these 21 articles potentially eligible for inclusion, after reviewing the full-text article, six articles were excluded as case reports or small case series [12][13][14][15][16][17], one due to data overlap [18], and three due to insufficient data to calculate sensitivity or specificity of 18 F-DOPA PET [19][20][21].…”
Section: Literature Searchmentioning
confidence: 99%